Use of haemostatic gel in the management of cervical pregnancy: a case report. (4th March 2021) - Han, Ji Yeon; Kim, Hoon; Kim, Sung Woo; Ku, Seung-Yup; Suh, Chang Suk; Kim, Seok Hyun
Abstract: Purpose: This case report aimed to describe haemostatic agents with systemic methotrexate (MTX) as an effective management for cervical pregnancy with bleeding. Case presentation: A 34-year-old nulligravida patient was referred due to vaginal spotting and lower abdominal discomfort, and was diagnosed with a cervical pregnancy at 6 weeks of gestation. The patient was treated with a multi-dose MTX regimen, and the bleeding was successfully controlled with haemostatic agents, which were applied at the bleeding site of the cervix. After completion of MTX treatment, beta human chorionic gonadotropin (β-hCG) decreased to undetectable range. Furthermore, patients could preserve her uterus and maintain fertility. Conclusion: Haemostatic agents can be regarded as an effective option for vaginal bleeding due to cervical pregnancy.